Remarks on the diversity and echolocation calls of hipposiderid bats (Chirroptera: Hipposideridae) in Cuc Phuong National Park, northeastern Vietnam - Thong (Academia Journal of Biology, 2023)
Cuc Phuong is the oldest and most well-known National Park in Vietnam. With its large primary forest area and karst cave systems, it is assumed to be an ideal home to a highly diverse bat fauna. However, species diversity and echolocation of bats in this park are poorly characterized. Between April 2021 and April 2022, three bat surveys were conducted in the park with special attention on the species of the family Hipposideridae. The bat specimens collected previously from the park were also examined. According to past records, hipposiderids in the park comprised at least seven species: Aselliscus stoliczkanus, Coelops frithii, Hipposideros alongensis, Hipposideros armiger, Hipposideros gentilis, Hipposideros lylei and Hipposideros poutensis. In this series of field surveys, six of these seven species were captured while Coelops frithii was only confirmed from specimen examination. Each species is clearly distinguishable by their morphology and echolocation calls. This study provides the first comparison of echolocation calls of all seven species which will be useful for potential acoustic identification and monitoring bats in the park and surrounding areas in future.